(untitled) (De Musica, 2021)
Developed and distributed in 2007 to promote the second version of the Vocaloid software, Hatsune Miku has quickly become a protean phenomenon. First and foremost, Hatsune Miku is a synthetic voice system that the spectator-listener can utilise to create and share custom compositions. Secondly, she is also a holographic celebrity performer appearing in live concerts, and the heroine of a video game series project DIVA. Thirdly, she is the protagonist of numerous fan fiction titles. Finally, since 2013, she is also the lead singer of an opera piece. In this paper, we focus on the Hatsune Miku case, an outstanding example of holography in pop music, which radicalise the question of fan attachment and celebrity, at the crossroads of technology, newly emergent economic models within cultural industries, fan culture and creative audiences.